Just One Shot? The Contextual Effects of Matched and Unmatched Intoxication on Perceptions of Consent in Ambiguous Alcohol-fueled Sexual Encounters - Laughlin, Ellen (Journal of interpersonal violence, 2023)
The current research examined how contextual factors—the quantity of alcohol consumed by each partner, and whether this quantity matched—influenced how alcohol-fueled sexual encounters were perceived with regard to consent, coercion, sexual assault, and perceived responsibility of the focal partner for the outcome of the encounter. Across four studies (Ntotal = 535), participants read vignettes in which one person described a sexual encounter they had following a night out drinking. These scenarios differed within studies as a function of quantified alcohol consumed (1 shot; 15 shots) and whether both people in the vignettes consumed the same amount of alcohol (matched; unmatched). They also differed between studies as a function of whether the couples described were mixed gender or same gender. Across all four studies, scenarios in which both people in the scenario consumed different quantities of alcohol (i.e., 15 vs. 1 shot) were seen as less consensual, more coercive, and more likely to be an assault compared to scenarios where consumption was matched, especially at lower levels of intoxication (i.e., 1 shot each vs. 15 shots each). However, focal partners were also seen as less responsible for the outcome of the interaction when levels of intoxication were unmatched compared to matched. This pattern replicated across scenarios depicting same-gender and mixed-gender couples. These findings suggest that people prioritize information regarding whether sexual partners are “matched” or “unmatched” in terms of their intoxication when evaluating whether ambiguous sexual encounters are consensual and perceived individual responsibility.